Characteristics, Prognosis, and Competing Risk Nomograms of Cutaneous Malignant Melanoma: Evidence for Pigmentary Disorders - Li, Zichao; Li, Xinrui; Yi, Xiaowei; Li, Tian; Huang, Xingning; Ren, Xiaoya; Ma, Tianyuan; Li, Kun; Guo, Hanfeng; Chen, Shengxiu; Ma, Yao; Shang, Lei; et al. (Frontiers in Oncology, 2022)
Purpose: Cutaneous malignant melanoma (CMM) always presents as a complex disease process with poor prognosis. The objective of the present study was to explore the influence of solitary or multiple cancers on the prognosis of patients with cutaneous malignant melanoma (CMM) to better understand the landscape of CMM. Methods: We reviewed the records of CMM patients between 2004 and 2015 from the Surveillance, Epidemiology, and End Results Program. The cumulative incidence function was used to represent the probabilities of death. A novel causal inference method was leveraged to explore the risk difference to death between different types of CMM, and nomograms were built based on competing risk models. Results: The analysis cohort contained 165,043 patients with CMM as the first primary malignancy. Patients with recurrent CMM and multiple primary tumors had similar overall survival status (P=0.064), while their demographics and cause-specific death demonstrated different characteristics than those of patients with solitary CMM (P<0.001), whose mean survival time are 75.4 and 77.3 months and 66.2 months respectively. Causal inference was further applied to unveil the risk difference of solitary and multiple tumors in subgroups, which was significantly different from the total population (P<0.05), and vulnerable groups with high risk of death were identified. The established competing risk nomograms had a concordance index >0.6 on predicting the probabilities of death of CMM or other cancers individually across types of CMM. Conclusion: Patients with different types of CMM had different prognostic characteristics and different risk of cause-specific death. The results of this study are of great significance in identifying the high risk of cause-specific death, enabling targeted intervention in the early period at both the population and individual levels.